REGIONAL COOPERATION IN CENTRAL ASIA AS SEEN FROM UZBEKISTAN - KAKHAROV, Jahangir (CENTRAL ASIA AND THE CAUCASUS, 2007)
The UNDP report for 20051 described the Central Asian economies of Soviet times as closely connected with the rest of the Soviet Union at the expense of their cooperation with the outside world. There is the opinion that the considerable investments of the Soviet period in physical infrastructure and human capital have somewhat improved the standard of living in this part of the Soviet world. The improvements, however, arrived with devastating effects on the environment and the region’s culture.In 1991, the new states (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uz- bekistan) with a total population of about 60 million rose from the ruins of what was once called the Soviet Union. The squabbles among some of these Soviet successor-states undermined regional trade and damaged the water and energy systems.Here I have undertaken an analysis of two important aspects of regional cooperation—trade and energy—using Uzbekistan and Tajikistan as examples. The main question is: What is interfering with closer regional cooperation in both fields and what should be done to improve the situation.To move forward the Central Asian economies should use their advantages and turn them into development factors:(a) the communicational, transportation, and energy infrastructure inherited from the Soviet Union makes a coordinated regional approach indispensable;(b) ecological problems call for concerted regional efforts;(c) the region’s potential attractiveness for foreign and local investors who would rather operate in regions free from trade and transit barriers than in small and limited economies;(d) regional cooperation is badly needed to move to the world markets to promote the region’s further integration into the world economy.After looking into two aspects of regional cooperation (trade and energy), I discovered that the road toward wider cooperation was blocked. In regional trade:—The ability to cooperate with neighbors depends on the development level of the country’s market economy and the mechanisms of democratic administration. So far, these factors remain undeveloped in Central Asia, which interferes with successful regional cooperation;—Different economic strategies result in different trade policies, which interferes with regional cooperation;—The Regional Trade Agreements among the Central Asian republics normally apply to a very limited range of commodities and are too complicated with respect to the commodities’ origin. For these reasons the majority of them remained on paper.